Implementasi Sikap Toleransi Sebagai Nilai Pendidikan Islam dalam Kehidupan Sosial Keagamaan Masyarakat Plural - Halimah, Lusi Nur; warsiyah, Warsiyah (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
This study aims to determine how the implementation of tolerance in the socio-religious life of a plural society in Dukuh Godang, Karangsari Village, Cluwak District. This research is categorized as qualitative using descriptive analytical method. Data collection techniques used were interviews, observations, and documentation with informants of Muslim and Buddhist religious leaders in Dukuh Godang, Karangsari Village, Cluwak District. This study is interesting because the tolerance attitude applied by the Muslims of Dukuh Godang, Karangsari Village, Cluwak District has a very important goal, namely so that non-Muslims are not anti-Islamic. Mutual respect, mutual love is intended to make them interested in Islam, because basically Islam is rahmatan lil 'alamin. That motivation has paid off. Since 1999-2022, it is recorded that 20 people have converted to Islam.Keywords: Â Tolerance, Religious Social, Plural.